2018
DOI: 10.1007/s10880-018-9569-4
|View full text |Cite
|
Sign up to set email alerts
|

Using Virtual Human Technology to Examine Weight Bias and the Role of Patient Weight on Student Assessment of Pediatric Pain

Abstract: The purpose of the study was to investigate the influence of weight bias and demographic characteristics on the assessment of pediatric chronic pain. Weight status, race, and sex were manipulated in a series of virtual human (VH) digital images of children. Using a web-based platform, 96 undergraduate students with health care-related majors (e.g., Health Science, Nursing, Biology, and Pre-Medicine) read a clinical vignette and provided five ratings targeting the assessment of each VH child's pain. Students al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…This may be an area that requires further attention in future research to ensure that care is not compromised. There is limited evidence on interventions to reduce weight bias [ 65 ], but simulated educational techniques have shown promise [ 66 , 67 ]. Inter professional research into methods to reduce weight bias and incorporating the patient’s voice have been called for [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be an area that requires further attention in future research to ensure that care is not compromised. There is limited evidence on interventions to reduce weight bias [ 65 ], but simulated educational techniques have shown promise [ 66 , 67 ]. Inter professional research into methods to reduce weight bias and incorporating the patient’s voice have been called for [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…This correlation suggests that delays in care for SCFE PLOS ONE patients may be more complex than previous research has indicated. Current healthcare providers acknowledge that unfavorable views toward obese patients exist, and multiple metareview studies have indicated these negative perceptions have persisted for many decades in the healthcare field [67][68][69][70][71]. Obese patients have reported feeling dismissed by their healthcare provider regarding pain concerns [67,71,72].…”
Section: Plos Onementioning
confidence: 99%
“…For example, several studies manipulated patient demographics and other contextual cues (e.g., high or low pain expression) using VPs to evaluate pain treatment disparities. 4 , 12 , 14–16 These studies utilized a web-based platform (e.g., Qualtrics) to present VPs to participants who then completed visual analog scales (VASs) and other self-report measures assessing their beliefs and pain treatment decisions. VP profiles typically consisted of a static image or brief video accompanied by a text vignette.…”
Section: Introductionmentioning
confidence: 99%